Percepatan Pengembangan Ekosistem Sektor Jasa Keuangan - Rahmayati Rahmayati (AGHNIYA : Jurnal Ekonomi Islam, 2021)
The financial system in general is an order in the economy of a country that has a role, especially in providing service facilities in the financial sector by financial institutions. This article aims to provide an overview and explanation of the acceleration of the development of the financial services sector ecosystem in Indonesia. The methodology of this article uses a study of related discussion literature. The results of this article prove that Indonesia has an achievement strategy to accelerate the development of the financial services sector ecosystem through the issuance of work programs, master plans, and published regulations.